The Application of Gorontalo Provincial Regional Regulation Number 4 of 2020 in the Efforts to Prevent and Control Covid-19 in Gorontalo City - Lani Cahyani Korompot (Universitas Negeri Gorontalo, 2019)
This article aims to find out how the application of Regional Regulation Number 4 of 2020 in efforts to prevent and control Covid-19. Based on the title raised in this study, the researchers used empirical research methods. The process of collecting data from the object studied in this study was by using interview techniques, document studies, and observation techniques. The application of the Gorontalo Provincial Regional Regulation Number 4 of 2020 concerning the application of Discipline and Law Enforcement of Health Protocols in the Efforts to Prevent and Control Covid-19 has been applied quite maximally by the government under the provisions of the duties that have been set and the authorities that have been coordinated which in this case includes all the efforts needed in handling Covid-19, this affirmation was supported by some information and also exploration carried out by researchers.